Comparative analysis of pre-operative findings and post-operative outcomes in primary and secondary macular holes at a tertiary eye hospital in South India - Shubham Darade; Rupal Kathare; Ayushi Choudhary; Gaurang Sehgal; Jay Chhablani; Kanika Godani; Naresh Kumar Yadav; Priyanka Gandhi; Prathiba Hande; Rubble Mangla; Vishma Prabhu; Ramesh Venkatesh (International Journal of Retina and Vitreous)
Abstract Purpose This study aimed to compare demographics, clinical characteristics, and post-surgical outcomes between idiopathic and secondary full-thickness macular holes (MHs). Methods A retrospective analysis of 348 eyes from 339 patients treated between June 2017 and December 2023 was conducted. The study included both idiopathic and secondary MHs, excluding cases where surgery was not performed or lacked sufficient follow-up. Demographic data, visual acuity (VA), ocular characteristics, and optical coherence tomography measurements were analyzed. Results Idiopathic MHs were identified in 308 eyes (89%), and secondary MHs in 40 eyes (11%). Idiopathic MH patients were older (mean age: 68.26 vs. 60.13 years; p = 0.001) and more commonly female (63% vs. 40%; p = 0.005). Post-surgical closure was achieved in 86% of all MHs, with a median VA improvement of 15 ETDRS letters (3 Snellen lines). However, secondary MHs had a lower closure rate (67% vs. 89%, p = 0.001) and less VA improvement (2 lines vs. 3 lines, p = 0.001) compared to idiopathic MHs. Significant differences in maximal basal diameter and diameter hole index were noted between the groups. Conclusions Secondary MHs, accounting for 11% of surgical cases, show poorer anatomical and visual outcomes than idiopathic MHs. Despite lower success rates, early surgical intervention in secondary MHs is recommended to enhance outcomes. Differentiating between idiopathic and secondary MHs is crucial for optimal management.